1981
DOI: 10.1017/s0515036100006802
|View full text |Cite
|
Sign up to set email alerts
|

Further Results on Recursive Evaluation of Compound Distributions

Abstract: A recent result by Panjer provides a recursive algorithm for the compound distribution of aggregate claims when the counting law belongs to a special recursive family. In the present paper we first give a characterization of this recursive family, then describe some generalizations of Panjer's result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(80 citation statements)
references
References 1 publication
1
78
0
1
Order By: Relevance
“…Observe that the initial value (5) simplifies to g 0 = q 0 for f 0 = 0. Sundt and Jewell (1981) showed that (3) holds precisely for the binomial, negative binomial and Poisson distribution (and, as a matter of course, for the degenerate distribution q 0 = 1).…”
Section: Panjer Recursionmentioning
confidence: 97%
“…Observe that the initial value (5) simplifies to g 0 = q 0 for f 0 = 0. Sundt and Jewell (1981) showed that (3) holds precisely for the binomial, negative binomial and Poisson distribution (and, as a matter of course, for the degenerate distribution q 0 = 1).…”
Section: Panjer Recursionmentioning
confidence: 97%
“…The famous Panjer recursion [20,29] is contained in the following theorem: Theorem 4.1 (Extended Panjer recursion). Assume that the probability distribution {q n } n2N 0 of N belongs to the Panjer(a, b, k) class and a P[X 1 = 0] 6 = 1.…”
Section: A Generalization Of the Panjer Recursionmentioning
confidence: 99%
“…All distributions belonging to a Panjer(a, b, k) class were identified by Sundt and Jewell [29] for the case k = 0, Willmot [33] for the case k = 1, and finally Hess, Liewald and Schmidt [11] for general k 2 N 0 . More general relations than (1.2) and corresponding recursion schemes have been considered in articles by Sundt [28], Hesselager [12], and Wang and Sobrero [31].…”
mentioning
confidence: 99%
“…This very popular set of claim number distributions was introduced in 1981 by Jewell and Sundt [21]. It is based on the simple recursion…”
Section: On Excess-of-loss Reinsurancementioning
confidence: 99%